Prispevek k poznavanju favne dvoživk (Amphibia) severovzhodne Slovenije - Lešnik, Aleksandra (Natura Sloveniae, 1999)
The results Of the work of the amphibiological group on the Student Biology Research Camp Središče ob Dravi 97 are presented. Of the 68 localities,12 species of amphibians were recorded from 23 JuIy and 2 August 1997. The main intention of the work was to survey the amphibian species and their habitats in the study area.
Keywords: Amphibia; dvoživke; Ecosystem; prevalence; razširjenost; zoogeografija